1970
DOI: 10.1111/j.1748-1716.1970.tb04757.x
|View full text |Cite
|
Sign up to set email alerts
|

Dilatation of a Medium‐Sized Artery Immediately after Local Changes of Blood Pressure and Flow as Measured by Ultrasonic Technique

Abstract: INOEBRIOTSEN, R. and S. LERAAND. Dilatation of a medium-sizcd artery immediately after local changes of blood pressure and flow as meaJured by ultrasonic terhnique. Acta physiol. scand. 1970. 79. 552-558. The effect of changes in blood pressure and flow on the calibre of the medium-sized artery has been studied in model experiments with an a-v fistula on the femoral vessels in dogs, On opening of the fistula a large local fall of blood pressure proximal to the fistula and an increase in flow up to 1000 74ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1970
1970
1995
1995

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 2 publications
2
8
0
Order By: Relevance
“…In addition, an ascending process is also excluded because the changes in blood flow were caused by an intervention distal to the capillary bed. This exclusion of an ascending dilatory signal is consistent with previous animal studies that documented an increase in conduit vessel size shortly after the creation of arteriovenous fistulae 3 and with studies where distal arterial sectioning did not abolish the upstream large vessel dilation following acute increments in blood flow. 4 Parenthetically, we should point out that resting flow in the dialysis patients was exceedingly high, and brachial artery size was substantially larger than the diameters noted in normal subjects.…”
Section: -2supporting
confidence: 90%
See 1 more Smart Citation
“…In addition, an ascending process is also excluded because the changes in blood flow were caused by an intervention distal to the capillary bed. This exclusion of an ascending dilatory signal is consistent with previous animal studies that documented an increase in conduit vessel size shortly after the creation of arteriovenous fistulae 3 and with studies where distal arterial sectioning did not abolish the upstream large vessel dilation following acute increments in blood flow. 4 Parenthetically, we should point out that resting flow in the dialysis patients was exceedingly high, and brachial artery size was substantially larger than the diameters noted in normal subjects.…”
Section: -2supporting
confidence: 90%
“…(Circulation Research 1989;64:32-42) T he ability of large blood vessels to alter their tone in response to acute alterations in blood flow has recently been documented in dog coronary 1 -2 and dog femoral arteries. 3 - 5 This process has been termed reactive dilation, 1 and it has been suggested that the process is truly localized to the large vessel and may require endothelial integrity. 5 A relation between increased blood flow and large vessel dilation in human subjects has not been previously described.…”
Section: Characteristics Of Flow-mediated Brachial Artery Vasodilatiomentioning
confidence: 99%
“…Systemic studies of the relationship between flow, diameter, and pressure in the femoral artery and other conduit vessels under steady-state conditions are in progress, and it is already apparent that larger increments in diameter can be induced by further increase in blood flow. Ingebrigtsen and Leraand (8), working in our laboratory, found that opening of an arteriovenous fistula resulted in an increase in arterial diameter of more than 1035,…”
Section: Discussionmentioning
confidence: 89%
“…It has been known for some time that an acute increase in blood flow, achieved either as a result of muscle con tractions [ 1,2] or A-V fistulae [3,4], can induce dilatation of homogeneous capillary perfusion. Several authors showed that long-term dilatation produced either by var ious drugs [6,7] or by long-term activity of skeletal mus cles, whether induced by endurance training [8] or electrial stimulation [9,10], led to growth of capillaries [II].…”
Section: Introductionmentioning
confidence: 99%